PENGOLAHAN MOTIF MENGGUNAKAN TEKNIK ESCHER DENGAN INSPIRASI TENUN IKAT SUMBA PADA BUSANA READY-TO-WEAR - Jeremi Samuel; Morinta Rosandini (Corak : Jurnal Seni Kriya, 2021)
Moving from the potencial of processing textile pattern with tessellation composititon using non-geometry elements. The technique called Escher’s technique which is used with inspiration from oramental variation of Sumba’s hinggi ikat weaving because it is using non-geometry elements too. The purpose of this research is for creating new variant of Ready-to-wear clothing. Mixed method applied in this research which is quantitative method by doing the experiment mathematically and qualitative method by doing observation about both  the used of tessellation composition and the characteristic of Sumba’s hinggi ikat weaving and literature study of Escher’s technique. Next is the experiment of  processing textile pattern by using Escher’s technique with the inspiration of ornamental variation of Sumba’s hinggi ikat weaving. The experiment results applied using surface design’s technique which is digital printing and embroidery accent and developed become menswear Ready-to-wear. The used of Escher’s technique for processing motif still can be developed with various inspirations.  Berangkat dari potensi pengolahan motif dengan komposisi tessellation menggunakan komponen nongeometri. Teknik yang digunakan disebut teknik Escher dengan inspirasi ragam hias tenun ikat hinggi Sumba karena tenun ikat hinggi Sumba memiliki ragam hias dengan unsur penyusun bidang nongeometri.Tujuan penelitian ini adalah untuk menciptakan variasi baru pada busana Ready-to-wear. Metode campuran digunakan pada peneltian ini, yaitu metode kuantitatif dengan melakukan penghitungan matematis pada saat proses eksperimen dan kualitatif dengan melakukan observasi penggunaan pattern dengan komposisi tessellation juga karakter tenun ikat hinggi Sumba dan studi pustaka mengenai teknik Escher. Dilanjutkan dengan proses eksperimen pengolahan motif secara digital menggunakan teknik Escher dengan inspirasi ragam hias tenun ikat hinggi Sumba. Hasil eksperimen diaplikasikan dengan teknik surface design, yaitu digital printing dan aksen bordir yang kemudian dikembangkan menjadi produk busana Ready-to-wear untuk pria. Penggunaan teknik Escher pada pengolahan motif dapat dikembangkan lagi dengan berbagai inspirasi.